Surface or bulk? Real-time manganese dissolution detection in a lithium-ion cathode. (1st August 2021) - Nikman, Shahin; Zhao, Dongni; Gonzalez-Perez, Violeta; Hoster, Harry H.; Mertens, Stijn F.L.
Abstract: The longevity of lithium-ion batteries is determined by the rate of chemical and electrochemical side reactions that limit their charge storage capacity. In particular, dissolution of transition metals from the cathode accelerates the blockage of Lix C6 anodes, but few direct dissolution studies have been made to date. Although LiMn2 O4 (LMO) has been frequently used as a model electrode for dissolution studies, the cause and nature of dissolution and dissolution-free states are still unclear. By online inductively coupled plasma analysis, we detect dissolution from LMO electrodes in real time to reveal the role of surface versus bulk structure effects, electrode potential and degree of lithiation on Mn dissolution. We find that fully lithiated LMO, with an average Mn redox state of 3.5, readily dissolves when brought in contact with 0.2 M Li2 SO4, but that on initial charging a dissolution–passivation event preceding delithiation abruptly stops further detectable dissolution, until well past fully delithiated λ-MnO2 . Dissolution reactivates on returning to the initial potential of pristine LMO, and increases exponentially in the overlithiation region. Our results provide access to much more detailed dissolution information than post-mortem battery analysis allows, enabling targeted materials screening and informing best practices in charging/discharging profiles. In particular, our data suggests that suitable potential conditioning of electrodes may mitigate dissolution, as an alternative or additional measure to the use of protective surface films or incorporation of dopants.